The Role of Affective Factors in Second Language Acquisition and Its Implications for Teaching - Li, Wenyao; Xu, Wenting (Pinnacle Academic Press Proceedings Series, 2026)
Against the backdrop of deepening globalization, second language acquisition has become an essential foundation for effective cross-cultural communication and educational development. This paper focuses on the role of affective factors in second language acquisition and examines their implications for classroom teaching. Drawing on major theoretical perspectives and illustrative empirical findings, it systematically explores the dual impact of affective variables such as motivation, self-confidence, and anxiety on learners’ engagement, strategy use, and long-term achievement. Existing studies indicate that positive emotions can significantly enhance attention, persistence, and willingness to communicate, whereas negative emotions may lead to cognitive overload, avoidance behaviors, and reduced language performance. Moreover, affective states and cognitive processes interact dynamically over time and across different learning contexts, rather than operating as isolated influences. In light of these insights, the paper argues for constructing an integrated “emotion–cognition” collaborative development model in language teaching. This model emphasizes the organic unity of language skill cultivation and learners’ psychological growth by optimizing the classroom emotional climate, fostering supportive teacher–student relationships, and adopting flexible, learner-centered instructional strategies. Practical implications include designing motivating tasks, providing constructive feedback, reducing debilitating anxiety, and encouraging self-regulation, so as to create a more effective and sustainable environment for second language learning.